Сharacteristics of the process of tolerance forming of senior pre-school children - Valentyna Liapunova (Vasyl Stefanyk Precarpathian National University, 2017)
The author devoted her paper to the actual aspect of the common problem of educationof tolerance of senior pre-school children. The author showed the characteristics of theprocess of tolerance forming of senior pre-school children, analyzed the main components ofthe process of tolerance forming of senior pre-school children such as content, aim, methodsand ways, described their meaning and gave their main characteristics. Key words: the process of tolerance forming of senior pre-school children; componentsof the process of tolerance forming of senior pre-school children; content, aim, methods andways of tolerance forming.